On the Problems of Amending the Terms of the Contract on the Provision of Tourism Services during the COVID-19 Pandemic - SEROHINA, Nataliia; PIKHURETS, Olena; SUKHATSKYI, Roman; YEVLAKHOVA, Elvira; LYTVYN, Stepan; MIROSHNYKOV, Ivan (Journal of Environmental Management and Tourism; Vol 12 No 1 (2021): JEMT 1(49) Spring 2021DO - 10.14505//jemt.v12.1(49).26, 2021)
The article is devoted to the content of legal instruments in terms of tourism business, namely the problem of amending the terms of the contract for tourism services. Attention has been drawn to the existence of the relationship between the activities of the tourism business and the existing legal framework, as well as the key provisions of the legal plane that regulates the rules, conditions, and level of responsibility in the provision of tourist services have been highlighted. The consequences of the negative impact on the activities of modern representatives of the tourism industry have been determined, and the need to revise the policy of providing tourist services in a pandemic caused by COVID-19 has been substantiated. Authors’ proposals for improving the legislative regulation of the tourism business in the context of the coronavirus have been provided, and a legal act that can positively influence the solution of existing problems has been proposed. The authors’ vision of the content of the package of measures that can positively influence not only the development of the tourism industry in general but primarily to help to identify those legal segments that need improvement in the future.